Structural characteristics of the economy of Mozambique: a SAM-based analysis - Arndt, Channing; Tarp, Finn (Wiley, 2000)
Key features of the Mozambican economy are synthesized in this paper based on a new 1995 social accounting matrix. Particular attention is paid to the critical role of home consumption and large marketing margins. The fundamental importance of agricultural development emerges clearly from the analysis in which the multiplier for value added by capital is re-examined. Agriculture has large sectoral multipliers and is generally more effective in the use of scarce capital than industry and services. Commodities with attractive features for the promotion of agriculture in the short to medium term include maize, rice, as well as small-scale livestock and forestry.